Nitrogen‐, water‐ and radiation‐use efficiencies affected by sugarcane breeding in Argentina - Acreche, Martin Moises (2017)
This study aimed to identify whether and how sugarcane (Saccharum spp.) breeding in Argentina modified nitrogen‐use efficiency (NUE), water‐use efficiency (WUE) and radiation‐use efficiency (RUE). Thirteen varieties were grown in two consecutive seasons. Trends in different traits were estimated by fitting the data to linear or bilinear regression models. There was a linear increase in NUE and WUE with the year of release throughout the 70‐year span, whereas water use was not modified by sugarcane breeding. There was a positive and strong (r > 0.90; P < 0.01) association between NUE and WUE and between sugar yield and NUE or WUE. Although RUE was not modified by sugarcane breeding, the amount of radiation intercepted by the crop increased with the year of release. Modern varieties had a higher maximum interception and needed fewer days to reach maximum interception than old varieties. This study suggests that applying ecophysiological knowledge would be instrumental in sugarcane breeding programmes in order to develop varieties with high resource‐use efficiency and capable to adapt to global climate change.